ADHERE: randomized controlled trial comparing renal function in de novo kidney transplant recipients receiving prolonged‐release tacrolimus plus mycophenolate mofetil or sirolimus. (28th November 2016) - Rummo, Oleg O.; Carmellini, Mario; Rostaing, Lionel; Oberbauer, Rainer; Christiaans, Maarten H. L.; Mousson, Christiane; Langer, Robert M.; Citterio, Franco; Charpentier, Bernard; Brown, Malcolm; Kazeem, Gbenga; Lehner, Frank; et al.
Summary: ADHERE was a randomized, open‐label, Phase IV study comparing renal function at Week 52 postkidney transplant, in patients who received prolonged‐release tacrolimus‐based immunosuppressive regimens. On Days 0–27, patients received prolonged‐release tacrolimus (initially 0.2 mg/kg/day), corticosteroids, and mycophenolate mofetil (MMF). Patients were randomized on Day 28 to receive either prolonged‐release tacrolimus plus MMF (Arm 1) or prolonged‐release tacrolimus (≥25% dose reduction on Day 42) plus sirolimus (Arm 2). The primary endpoint was glomerular filtration rate by iohexol clearance (mGFR) at Week 52. Secondary endpoints included eGFR, creatinine clearance (CrCl), efficacy failure (patient withdrawal or graft loss), and patient/graft survival. Tolerability was analyzed. The full‐analysis set comprised 569 patients (Arm 1: 287; Arm 2: 282). Week 52 mean mGFR was similar in Arm 1 versus Arm 2 (40.73 vs. 41.75 ml/min/1.73 m 2 ; P = 0.405), as were the secondary endpoints, except composite efficacy failure, which was higher in Arm 2 versus 1 (18.2% vs. 11.5%; P = 0.002) owing to a higher postrandomization withdrawal rate due to adverse events (AEs) (14.4% vs. 5.2%). Results from this study show comparable renal function between arms at Week 52, with fewer AEs leading to study discontinuation with prolonged‐release tacrolimus plus MMF (Arm 1) versus lower dose prolonged‐release tacrolimus plus sirolimus (Arm 2).